# Evaluate the given expression |-4b-8| + |-1-b^{2}| + 2b^{3} for b = -2

Algebraic Expression is made up of variables and constants along with algebraic operations such as addition, subtraction, etc.. these Expressions are made up of terms. Algebraic expressions are the equations when the operations such as addition, subtraction, multiplication, division, etc. are operated upon any variable.

A combination of terms by the operations such as addition, subtraction, multiplication, division, etc is termed as an algebraic expression (or) a variable expression.

e.g.: 2x + 4y – 7, 3x – 10, etc.

The above expressions are represented with the help of unknown variables, constants, and coefficients. The combination of these three terms is termed as an expression. Unlike the algebraic equation, it has no sides or ‘equals to’ sign.

**Types of Algebraic Expression**

Algebraic Expressions are of three types based on the number of terms in the expression:

- Monomial Expression
- Binomial Expression
- Polynomial Expression

**Monomial Expression**

An expression that has only one term is termed a Monomial expression.

Examples of monomial expressions include 5x

^{4}, 3xy, 2x, 5y, etc.

**Binomial Expression**

An algebraic expression which is having two terms and unlike are termed as a binomial expression

Examples of binomial include 2xy + 8, xyz + x

^{2}, etc.

**Polynomial Expression**

An expression that has more than one term with non-negative integral exponents of a variable is termed a polynomial expression.

Examples of polynomial expression include ax + by + ca, x

^{3}+ 5x + 3, etc.

**Other Types of Expression**

We have other expressions also apart from monomial, binomial, and polynomial types of expressions which are

- Numeric Expression
- Variable Expression

**Numeric Expression**

An expression that consists of only numbers and operations, but never includes any variable is termed a numeric expression.

Some of the examples of numeric expressions are 14 + 5, 18 ÷ 2, etc.

**Variable Expression**

An expression that contains variables along with numbers and operations to define an expression is termed as A variable expression.

Some examples of a variable expression include 4x + y, 5ab + 53, etc.

**Some Important Algebraic Formulas**

There are some terms of algebraic expression which basically used,

(a + b)

^{2}= a^{2}+ 2ab + b^{2}(a – b)

^{2}= a^{2}– 2ab + b^{2}(a + b)(a – b) = a

^{2}– b^{2}(x + a)(x + b) = x

^{2 }+ x(a + b) + ab(a + b)

^{3}= a^{3}+ b^{3 }+ 3ab(a + b)(a – b)

^{3}= a^{3}– b^{3}– 3ab(a – b)a

^{3}– b^{3}= (a – b)(a^{2}+ ab + b^{2})a

^{3}+ b^{3}= (a + b)(a^{2}– ab + b^{2})

**Example: If 2x ^{2}+3xy+4x+7 is an algebraic expression. Determine the equation.**

**Solution:**

2x

^{2}, 3xy, 4x, and 7 are the TermsCoefficient of term: 2 is the coefficient of x

^{2}Constant term: 7

Variables: here x, y are variables

Factors of a term: If 2xy is a term, then its factors are 2, x, and y.

### Evaluate the given expression |-4b-8| + |-1-b^{2}| + 2b^{3} for b = -2.

**Solution: **

Given term : b = -2

= |-4b-8|+|-1-b

^{2}|+2b^{3}= |-4(-2)-8|+|-1-(-2)

^{2 }|+2(-2)^{3}= |8 -8|+|-1- 4 |+2(-8)

= |0 |+|-5 | – 16 {modulus always gives positive value}

= 5 – 16

= -11

**Similar Problems **

**Problem 1: Add 6x ^{2}–7x+3, –8x^{2}+2x–5 and 7x^{2}–x–2**

**Solution:**

Given: 6x

^{2}–7x+3, –8x^{2}+2x–5 and 7x^{2 }– x – 2Now add the like terms together

= {6x

^{2}+ (-8x^{2}) + 7x^{2}} + {(-7x) + 2x -x} + {3 -5 -2}= {6x

^{2}– 8x^{2}+ 7x^{2}} + {-7x + 2x – x} + (-4)= 5x

^{2}+ (-6x) – 4= 5x

^{2}-6x – 4

**Problem 2: Simplify: 9 – 3(x – 1)**

**Solution:**

Here we have

9 – 3(x – 1)

= 9 – 3x +3

= 12 – 3x

= -3x + 12

= -3( x – 4 )

**Problem 3: Simplify (x ^{2} + 18x +81)/(x^{2} – 64) × (x + 8)/(x + 9).**

**Solution:**

Given that : (x

^{2}+ 18x +81)/(x^{2}– 64) × (x + 8)/(x + 9).= (x

^{2}+ 18x +81)/(x^{2}-64) × (x + 8)/(x + 9)By factorizing the above terms

= {(x+9)(x + 9) / (x

^{2}– 8^{2})} × {(x + 8)/(x+9)}By using a

^{2}– b^{2}= (a + b) (a – b)= {(x+9)(x + 9) / (x – 8)(x + 8)} × {(x + 8)/ (x+9)}

By simplifying

= (x + 9)(x – 8)